Four-Frame Leadership Orientations and Job Performance Amongst Jakarta Working Adults - Christanto Hung, Gary; Chan Yin Fah, Benjamin; Kwok Wai Wong, Robby (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the differences in leadership orientations on employee job performance in the context of Bolman and Deal’s four-frame leadership theory and highlighted on whether there are any differences with the younger generation. Information for the study was gathered through self-administered questionnaire and nonprobability convenience sampling method. A total of 180 completed and usable questionnaires have been gathered up amongst working adults in Jakarta. The findings revealed that different variables yielded different influences for leadership orientations and job performance in terms of gender, age, marital status, job position, and length of work. In four-frame leadership types, Symbolic Frame has the most significant influence for job performance, compared with Political Frame that has the lightest influences. The regression analysis shows that Structural Frame and Symbolic Frame are the predictors for job performance. This study is important to assist potential leaders to adapt better with Jakarta’s working condition. It is vital for leaders to realize how to increase and maintain good job performance by acknowledging the importance of having different leadership type, which also could help organizations to choose the right leaders or managers that can lead them toward success.